4-Hydroxy-3-methoxybenzaldehyde-nicotinamide (1/1) - How, Fiona Ni Foong; M.S, Amalina; Khaledi, Hamid; Mohd Ali, Hapipah (Wiley-Blackwell Publishing, Inc., 2011)
In the title compound, C6H6N2O.C8H8O3, an equimolar cocrystal of nicotinamide and vanillin, the aromatic ring and the amide fragment of the nicotinamide molecule make a dihedral angle of 32.6 (2)deg. The vanillin molecule is almost planar, with an r.m.s. deviation for all non-H atoms of 0.0094 angstrom . The vaniline and nicotinamide aromatic rings are nearly coplanar, the dihedral angle between them being 3.20 (9)deg. In the crystal, the two components are linked through N—H...O and O—H...N hydrogen bonds into chains along the a axis.The chains are connected via C—H...O interactions, forming a three-dimensional polymeric structure.